Konsep Pendidikan Islam Holistik Melalui Pendekatan Berbasis Nilai-Nilai Teologis Normatif - Muhammad Ja'far; Ja'far, Muhammad; Rahim, Fathor; Maknin, Nur Afifah Khurin (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
This study aims to present an analysis of the dynamics of Islamic education in Indonesia. Islamic education in Indonesia currently continues to experience a fluctuating process and moves dynamically to adapt to changing times. Of course this makes policy makers who are members of a government institution must quickly respond to changing times by providing a reflection of what must be improved and perfected. This research aims to provide a new paradigm through a theological-normatif approach based on the Qur'an and Sunnah to perfect the concept of Islamic education. This research uses the systematic literature review (SLR) method. The results of this study found that the basis of tawhid correlated with theological values and the Koran hadith correlated with normatif aspects has a positive construction that can develop Islamic education in a more holistic and comprehensive direction. In fact, many Muslim figures and scholars view that the normatif theological aspect in Islamic education can form a complete individual.